Glacial-interglacial sedimentation control on gas seepage exemplified by Vestnesa Ridge off NW Svalbard margin - Rasmussen, Tine L.; Nielsen, Tove (Frontiers in Earth Science, 2024)
Vestnesa Ridge is built-up of thick contourites mainly deposited during the last ~5 million years. Methane leaks from deep gas reservoirs creating pockmarks on its crest, and which have been the focus of numerous studies. Sedimentation patterns in relation to the pronounced changes in oceanography and climate of the last glacial-interglacial cycles and its possible impact of seepage of gas have rarely been studied. Here, we present a detailed history of contourite development covering the last ~130,000 years with most details for the last 60,000 years. The study is based on 43 marine sediment cores and 1430 km of shallow seismic lines covering the ridge including methane seep sites, with the purpose of reconstructing changes in depositional patterns in relation to paleoceanographical changes on glacial, interglacial, and millennial time scale in relation to activity of seepage of gas. The results show that thick Holocene deposits occurred below ~1250 m water depth in the western part of the ridge. Both in pockmarks at western and eastern Vestnesa Ridge, seepage decreased at ~10-9 ka in the early Holocene. The fine Holocene mud likely reduced seepage to a slow diffusion of gas and microbial oxidation probably prevented escape from the seafloor. Results also showed that seepage of gas was highly variable during the glacial, and low to moderate during the cold Heinrich stadial H1 (19-15 ka) and Younger Dryas stadial (13-12 ka). Seepage reached a maximum during the deglaciation in the Bølling and Allerød interstadials 15-13 ka and early Holocene 12-10 ka. The deglaciation was a period of rapid climatic, oceanographic, and environmental changes. Seepage of gas varied closely with these events indicating that slower tectonic/isostatic movements probably played a minor role in these millennial scale rapid fluctuations in gas emission.